E-cadherin and calretinin as immunocytochemical markers to differentiate malignant from benign serous effusions - He, Dong-Nan (World J Gastroenterol, 2004)
AIM: To investigate the expressions of E-cadherin and calretinin in exfoliated cells of serous effusions and evaluate their values in distinguishing malignant effusions from benign ones. METHODS: Fresh serous effusion specimens were centrifuged and exfoliated cells were collected. Cells were then processed with a standardized procedure, including paraformaldehyde fixation, BSA-PBS solution washing and smears preparation. E-cadherin and calretinin were detected by immunocytochemistry (ICC). RESULTS: In the exfoliated cells of serous effusions, most of carcinoma cells only expressed E-cadherin, and most of mesothelial cells only expressed calretinin, and benign cells (lymphocytes and granulocytes) did not express either of them. For E-cadherin, 85.7% (30/35) of malignant effusions and 8.1% (3/37) of benign fluids were ICC-positive (P < 0.001). The sensitivity of E-cadherin ICC in the diagnosis of malignant effusions was 85.7%, specificity 91.9%, and diagnostic rate 88.9%. For calretinin, 94.6% (35/37) of benign effusions and 11.4% (4/35) of malignant effusions were ICC-positive (P < 0.001). The sensitivity of calretinin ICC in the diagnosis of benign effusions was 94.6%, specificity 88.6%, and diagnostic rate 91.7%. For diagnosis of benign and malignant effusions by combining E-cadherin ICC and calretinin ICC, the specificities were up to 100% and 97.1%, respectively. CONCLUSION: E-cadherin ICC and calretinin ICC are sensitive and specific in differential diagnosis of benign and malignant serous effusion specimens and specificities are evidently improved when both markers are combined.